Integrating MaxEnt and InVEST modeling methods to identify priority areas for the conservation of emblematic and endemic wildlife in the Peruvian Tropical Andes - Gerson Meza-Mori; Shekoufeh Nematollahi; Carlos A. Amasifuen Guerra; Manuel Oliva-Cruz; Elver Coronel-Castro; Cristóbal Torres Guzmán; Asef Darvishi (Global Ecology and Conservation, 2025)
The habitat of emblematic and endemic species in the Tropical Andes of Peru is particularly vulnerable to environmental degradation due to anthropogenic activities. This study aimed to identify new spatial priority areas for the conservation of two endemic (Aotus miconax and Lagothrix flavicauda) and one emblematic (Tremarctos ornatus) fauna species in the Peruvian Tropical Andes (PTAs). In order to establish an innovative approach to conservation planning, we conducted the MaxEnt-InVEST modeling method, integrating the threatened species distribution and habitat quality models. The analysis revealed that 79.00 % of the integrated model priorities of conservation areas (IMPCA) are currently unprotected, and about 21.05 % of the IMPCA are identified as high-priority zones or core zones that fall outside the boundaries of the existing natural protected areas (NPAs) within the PTAs. While the IMPCA are distributed throughout the PTA, a greater density is observed in the northern zone. In addition, only 12.80 % of the IMPCA is within the current NPAs. Also, 8.20 % of the area is not included in the integrated model. Finally, 30.87 % of the IMPCA has been allocated to the current degraded areas identified by the Peruvian government. Consequently, it is imperative to advocate for collective action to restore these areas for the benefit of the species A. miconax, L. flavicauda and T. ornatus, as well as biodiversity and sustainable development. The integrative MaxEnt-InVEST method is a powerful tool for conservation policy because of it provides useful data that can support decisions at national and international levels to assess the effectiveness of NPAs in maintaining ecological functionality. These results provide valuable insights for policy makers and conservation practitioners in their efforts to protect and sustainably manage the unique biodiversity of the PTAs.